Ferns diversity comparison at permanent plot of Ulu Kimanis and Gunung Alab, Crocker Rang Park, Sabah - Nurul 'Afifah Abu Samah (2008)
A study was conducted to show if there is a difference in ferns diversity between areas of different altitudes, namely (i) Ulu Kimanis (600 m) and (ii) Gunung Alab (1800 m). This study was based on 30 mx 30 m study plots at each site. Distribution pattern of each fern species were determined at both study plots. Nine subplots of 10 mx 10 m were selected in each study plot. Each subplot was divided into 100 smaller divisions for coordinate reading. Seven species of five families were found at Ulu Kimanis and 24 species of nine families were found at Gunung Alab. The ferns studied are terrestrial ferns and those epiphytic ferns located two meter above ground. Gunung Alab has significantly higher species diversity compared to Ulu Kimanis (p < 0.05; where p value is based on Mann- Whitney U Test). There is no similarity (Sorensen Index = 0) between study plots, reflecting beta diversity is at its highest. Based on Morisita's Index, both plots showed a contagious distribution pattern of ferns. However, distribution patterns of both plots show a combination of contagious and uniform distribution pattern when visualized with scatter plots. This difference is due to the plot size, which is not sufficiently big to capture adequate data